USING GRADING TO SUPPORT STUDENT LEARNING - Townsley, Matt ([S.l.] : ROUTLEDGE, 2022)
Using Grading to Support Student Learning offers an accessible foundation for using grading practices to support student learning through classroom assessment. Purposeful, defensible grading and reporting mechanisms cannot be neglected in today's reform climate, and new approaches are needed to understand and refine the roles of homework, formative and summative assessments, and standards across grade levels. Evidence-based and full of illustrative examples, this book bridges research and theory on grading and assessment with classroom practices for pre-service and in-service teachers and fresh perspectives for educational researchers studying grading practices.
Keywords: EDUCATION / Teaching Methods & Materials / General; EDUCATION / Testing & Measurement; EDUCATION / Evaluation; Educational tests and measurements -- United States; Grading and marking (Students) -- United States